2022
DOI: 10.3390/ijerph19105853
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Algae-Based Measurements of the Toxicity of 14 Manufactured Nanomaterials

Abstract: With the increasing use of nanomaterials in recent years, determining their comparative toxicities has become a subject of intense research interest. However, the variety of test methods available for each material makes it difficult to compare toxicities. Here, an accurate and reliable method is developed to evaluate the toxicity of manufactured nanomaterials, such as Al2O3, carbon black, single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), CeO2, dendrimers, fullerene, gold, iron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This property of BSA has been reported in the past, and the phenomenon of lowering the toxicity level of chemicals, including that of manufactured nanomaterials, has been reported [ 35 , 36 , 37 ]. Authors reported EC50 values measured by the same dispersion method [ 38 ]: Al 2 O 3 : 53.9 ± 10.2 mg/L, carbon black: 4.8 ± 2.2 mg/L, MWCNTs: 9.0 ± 1.5 mg/L, CeO 2 : 26.2 ± 4.6 mg/L, dendrimers: 24.6 ± 3.9 mg/L, fullerene: 395.3 ± 51.6 mg/L, Au: 352.6 ± 137.3 mg/L, Fe: 64.3 ± 10.6 mg/L, nanoclays: 11,245.6 ± 2342.3 mg/L, Ag: 0.3 ± 0.04 mg/L, SiO 2 : 211.3 ± 22.7 mg/L, and ZnO: 0.06 ± 0.04 mg/L. These ecotoxicity test results suggest that applying the dispersion method for nanomaterials proposed in this study to the 14 manufactured nanomaterials included in the OECD’s Sponsorship Programme for the Testing of Manufactured Nanomaterials poses no problems.…”
Section: Resultsmentioning
confidence: 99%
“…This property of BSA has been reported in the past, and the phenomenon of lowering the toxicity level of chemicals, including that of manufactured nanomaterials, has been reported [ 35 , 36 , 37 ]. Authors reported EC50 values measured by the same dispersion method [ 38 ]: Al 2 O 3 : 53.9 ± 10.2 mg/L, carbon black: 4.8 ± 2.2 mg/L, MWCNTs: 9.0 ± 1.5 mg/L, CeO 2 : 26.2 ± 4.6 mg/L, dendrimers: 24.6 ± 3.9 mg/L, fullerene: 395.3 ± 51.6 mg/L, Au: 352.6 ± 137.3 mg/L, Fe: 64.3 ± 10.6 mg/L, nanoclays: 11,245.6 ± 2342.3 mg/L, Ag: 0.3 ± 0.04 mg/L, SiO 2 : 211.3 ± 22.7 mg/L, and ZnO: 0.06 ± 0.04 mg/L. These ecotoxicity test results suggest that applying the dispersion method for nanomaterials proposed in this study to the 14 manufactured nanomaterials included in the OECD’s Sponsorship Programme for the Testing of Manufactured Nanomaterials poses no problems.…”
Section: Resultsmentioning
confidence: 99%
“…While algae-derived natural products are generally considered safe, comprehensive safety evaluations are essential to determine the potential adverse effects and establish appropriate dosage guidelines [ 139 ]. Toxicity studies, including acute and chronic toxicity assessments, should be conducted to ensure the safety of algae-based interventions [ 140 ]. Furthermore, long-term studies are needed to evaluate the potential for the accumulation of algae-derived compounds in tissues or organs [ 31 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%